Penguatan Kapasitas Aparatur Desa Semamung Melalui Pelatihan OpenSID - Erwin Mardinata; Ryan Suarantalla; Tomy Dwi Cahyono; Jannatun Aliyah; Wilia Ismiyarti; Irawati; Hasri, Diah Anggeraini Hasri; Reza Muhammad Rizqi; Ayu Levia Tryana (Abdimas Indonesian Journal, 2025)
This community service activity (PkM) aims to increase the capacity of the Semamung Village apparatus through training in the use of the Open Source-based Village Information System, namely OpenSID. Semamung Village faces challenges in data management and public services due to dependence on manual systems. The main problems found were the lack of knowledge of the apparatus related to information technology, inadequate infrastructure, and resistance to system changes. To address these issues, a phased and comprehensive training method was applied, including introduction, hands-on practice, and ongoing mentoring. The results of the training showed a significant improvement in the apparatus' understanding and ability to use OpenSID, which resulted in administrative efficiency and transparency in village data management. In conclusion, the implementation of OpenSID in Semamung Village not only strengthens the capacity of the apparatus, but also paves the way for better public service improvement. The results of this service are expected to serve as a model for other villages in adopting information technology to improve governance that is more transparent and accountable.